Transforming school policy and practice : a case study of a participant observer environmental education teacher at St Francis Adult Education Centre - Torr, Ross (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1996.